Effect modifications of parents’ age at childbirth on association between ambient particulate matter and children obesity - Xianzhi Li; Bin Yu; Yajie Li; Haorong Meng; Zonglei Zhou; Shunjin Liu; Yunyun Tian; Xiangyi Xing; Yingchao Lei; Li Yin (BMC Public Health)
Abstract Background There is limited evidence regarding the modifying effects of parents’ age at childbirth on the relationship between air pollution and obesity in plateau areas. This study aimed to explore the association between particulate matter (PM) and child obesity, specifically investigating whether parents’ age at childbirth could modify this relationship in the Tibetan plateau, China. Methods Satellite-based random forest models were used to estimate the concentrations of PM2.5 (particulate matter with aerodynamic diameters ≤ 2.5 μm), PMc (particulate matter with aerodynamic diameters between 2.5 μm and 10 μm), and PM10 (particulate matter with aerodynamic diameters ≤ 10 μm). Linear and logistic regression models were employed to assess associations between PM exposure and obesity indicators, and effect estimates of PM across different particle sizes were compared. Results The study comprised 2,015 children under five years old. Postnatal exposure to PM was positively associated with overweight and obesity (OWO), waist-to-hip ratio (WHR) and body mass index (BMI). Among these pollutants, PM10 exhibited the strongest association with BMI and OWO, whereas PMc showed the strongest association with WHR. An interquartile range (IQR) increase in PM2.5 (5.67 µg/m3), PMc (5.25 µg/m3), and PM10 (11.06 µg/m3) was positively associated with OWO (odd ratio [OR] for PM2.5 = 1.52, 95% confidence interval [CI] for PM2.5 = 1.24 to 1.85; OR for PMc = 1.50, 95% CI for PMc = 1.19 to 1.88; OR for PM10 = 1.56, 95% CI for PM10 = 1.25 to 1.96), respectively. Stratified analysis by parents’ age at childbirth indicated that the effects of PM on obesity indicators were more pronounced in the advanced age group. Conclusions Long-term exposure to PM was positively associated with OWO, WHR, and BMI. Our findings also underscore the importance of examining the effects of ambient PM exposure on OWO, particularly in parents of advanced age at childbirth.